Development of low normal force contact using electro fine forming and lithography technology - Bhuiyan, Moinul; Yamada, Shinji; Kurokawa, Noriharu; Sakamoto, Katsuhiko; Takemasa, Eiichiro (2008)
This new technology is realized by Photo Resist Lithography and NiCo Electro Fine Forming Process, and enables the design of a small contact spring for applications requiring high density, high speed and high durability. The evaluation result proved the capability of Low Normal Force (0.10N-0.15N at 0.3mm) at contact point (5μm radius), durability of 100,000 contact cycles (less than 50mΩ).